Development of ELISAs for the detection of vitellogenin in three marine fish from coastal areas of China. (August 2018) - Li, Yuejiao; Wang, Jun; Zheng, Mingyi; Zhang, Yabin; Ru, Shaoguo
Abstract: Estrogenic pollution has aroused great concern for its adverse effects on marine organisms. This study aimed to establish biomarker-based methods for detecting environmental estrogens using vitellogenin (Vtg) of teleost fishes inhabiting coastal areas of China. Firstly, Vtgs in marbled flounder ( Pseudopleuronectes yokohamae ), black rockfish ( Sebastes schlegelii ) and fat greenling ( Hexagrammos otakii ) were purified, characterized and used to prepare antibodies. Then, Vtg ELISA for each species was developed using purified Vtg and its antibody. Marbled flounder Vtg ELISA had a working range of 3.9–500 ng/mL and a detection limit of 2.1 ng/mL, and black rockfish Vtg ELISA had strong cross-reactivity with marbled flounder Vtg. Furthermore, Vtg induction in male marbled flounder exposed to pentadecafluorooctanoic acid (PFOA) was measured by developed ELISA. Plasma Vtg concentrations were significantly increased with PFOA concentrations in seawater and fish muscle. Therefore, Vtg ELISAs for these species might be useful tools for monitoring marine environmental estrogens. Highlights: Sandwich ELISAs for Vitellogenins (Vtgs) of three marine fishes were established. Black rockfish Vtg ELISA had strong cross-reactivity with marbled flounder Vtg. The use of Vtg as a biomarker for marine estrogenic pollution was confirmed. Fish muscle had high bioaccumulation capability of PFOA from seawater. Plasma Vtg levels were significantly increased with muscle PFOA concentrations.